Kontribusi Kualitas Layanan Pendidikan, Citra Sekolah, Budaya Sekolah dan Biaya Pendidikan terhadap Keputusan Siswa Melanjutkan Pendidikan ke SMA Swasta di Kecamatan Buleleng - Luh Eka Wahyuni; I Gusti Ketut Arya Sunu; I Putu Wisna Ariawan (Pascasarjana Universitas Pendidikan Ganesha, 2023)
This study aims to 1) find out how much the quality of education services contributes to students' decisions to continue their education to private high schools in the Buleleng sub-district, 2) find out how much the school's image contributes to students' decisions to continue their education to private high schools in the Buleleng sub-district, 3) find out how the large contribution of school culture to students' decisions to continue their education to private high schools in the Buleleng sub-district, 4) find out how much the contribution of education costs to students' decisions to continue their education to private high schools in the Buleleng sub-district, 5) find out how the quality of education services, school image, school culture contributes, and the cost of education on students' decisions to continue their education to private high schools in the Buleleng sub-district. In this regard, the study was designed as a quantitative study using a sample of 73 people from a population of 731 private high school students. Sampling members using proportionate stratified random sampling technique. The independent variables in this study are the quality of education services, school image, school culture and education costs. While the dependent variable is the student's decision. Data was collected using the questionnaire method which was then analyzed using multiple linear regression analysis. The results showed that: (1) there was a significant contribution to the quality of education services to student decisions by 34.6%, (2) there was a significant contribution to school image to student decisions by -12.97%, (3) there was a significant contribution to culture schools to student decisions by 47,9%, (4) there is a significant contribution of education costs to student decisions by 30% and (5) there is a significant contribution simultaneously between the quality of education services, school image, school culture and education costs on student decision making by 81.2% and the remaining 18.8% is explained by other variables outside the research.